Peningkatan Kemampuan Berpikir Statistis Mahasiswa S1 Melalui Pembelajaran MEAs yang Dimodifikasi (Jurnal Infinity, 2012)
This paper contains the results of research on improving the ability to think statisis S1 students through the learning model-eliciting Activities (MEAs) are modified from the MEAs that have been developed by Garfield, Delmas and Zieffler (2010) by entering the didactical Design Research (DDR) when creating instructional materials , In this research, quasi experimental method with a pretest-posttest design. Research carried out on all students S1 Department of Mathematics Education of a State in Bandung who are following the lecture Basic Statistics on odd semester of 2011/2012 academic year. In the control class (class A student Pend Prodi. Mat force 2010/2011 39) were given conventional learning while the experimental class 1 (student of class B Prodi Pend. Mat force 2010/2011 41 people) and the experimental class 2 (student Prodi Pend. Mat force repeating 2008/2009 Basic Statistics 12 persons) were given a modified learning MEAs. Furthermore, in each class, the students were divided into three groups: high, medium and low based on a score initial capability test results statistically (TKAS). Data on statistical thinking skills students thinking skills obtained through statistical tests (TKBS), while the disposition of the statistical data is obtained by using scale student disposition. The results showed that there are differences in the increase in the ability to think statistically significant student between the control class, the experimental class 1 and class experiment 2. Increased statistical thinking skills students use learning MEAs modified significantly higher compared to students using conventional teaching. There are differences increase student statistically significant disposition between the control class, the experimental class 1 and class experiment 2. Improved statistical disposition of students who use the learning MEAs modified significantly higher compared to students using conventional teaching.